2005
DOI: 10.2135/cropsci2003.0678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salicylic Acid on Heat Tolerance Associated with Antioxidant Metabolism in Kentucky Bluegrass

Abstract: tase and CAT are the most effective antioxidant enzymes in scavenging AOS (Bowler et al., 1992).Turf quality of Kentucky bluegrass (Poa pratensis L.) often declines during summer when temperatures exceed its optimum range.Various cultural practices such as irrigation, fertiliza-This study was designed to determine whether application of salicylic tion, and soil cultivation have been extensively investiacid (SA) to the shoots and soil could improve heat tolerance of gated to improve turf performance in cool-sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
107
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(120 citation statements)
references
References 37 publications
12
107
1
Order By: Relevance
“…Although the present measurements of water content were not significant between transgenic and wild type plants, the former did exhibit higher water content than wild type plants. Moreover, another study found 0.25 mmol salicylic acid (SA) to be most effective in enhancing heat tolerance in Kentucky bluegrass, which was manifest by improved re-growth potential following heat stress of 72 h and maintenance of leaf water content at 77% during the 12 h stress period similar to that under normal temperature conditions (18). Heat stress was associated with a 3.6% higher water content in Kentucky bluegrass plants as compared with untreated plants (18).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present measurements of water content were not significant between transgenic and wild type plants, the former did exhibit higher water content than wild type plants. Moreover, another study found 0.25 mmol salicylic acid (SA) to be most effective in enhancing heat tolerance in Kentucky bluegrass, which was manifest by improved re-growth potential following heat stress of 72 h and maintenance of leaf water content at 77% during the 12 h stress period similar to that under normal temperature conditions (18). Heat stress was associated with a 3.6% higher water content in Kentucky bluegrass plants as compared with untreated plants (18).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide concentrations were measured by monitoring the absorbance at 410 nm of the titaniumperoxide complex according to He et al (2005). One mL of supernatant extracted with cold acetone was added to 0.1 mL 20% titanium reagent and 0.2 mL 17 mol ammonia solution.…”
Section: Determination Of Hydrogen Peroxide (H 2 O 2 ) Contentmentioning
confidence: 99%
“…A promising area for increasing resistance of crops to thermal stress is by the use of chemical treatments like salicylic acid, abscisic acid and calcium chloride (Larkindale and Knight 2002;Chakraborty and Tongden 2005;He et al 2005). Acquisition of thermotolerance is likely to be of particular importance to plants that experience daily temperature fluctuations and are unable to escape to more favorable environments.…”
Section: Introductionmentioning
confidence: 99%